The learning rate in three dimensional high definition video assisted microvascular anastomosis in a rat model - Kotsougiani, Dimitra; Hundepool, Caroline A.; Bulstra, Liselotte F.; Shin, Delaney M.; Shin, Alexander Y.; Bishop, Allen T. (Journal of plastic, reconstructive & aesthetic surgery, 2016)
Three-dimensional (3D) high definition (HD) video systems are changing microsurgical practice by providing stereoscopic imaging not only for the surgeon and first assistant using the binocular microscope, but also for others involved in the surgery. The purpose of this study was to evaluate the potential to replace the binocular microscope for microarterial anastomoses and assess the rate of learning based on surgeons' experience. Two experienced and two novice microsurgeons performed a total of 88 rat femoral arterial anastomoses: 44 using a 3D HD video device (‘Trenion’, Carl Zeiss Meditech) and 44, a binocular microscope. We evaluated anastomosis time and modified OSATS scores as well as the subjects' preference for comfort, image adequacy and technical ease. Experienced microsurgeons showed a steep learning curve for anastomosis times with equivalent OSATS scores for both systems. However, prolonged anastomosis times were required when using the novel 3D-HD system rather than direct binocular vision. Comparable learning rates for anastomosis time were demonstrated for novice microsurgeons and modified OSATS scores did not differ between the different viewing technologies. All microsurgeons reported improved comfort for the 3D HD video system but found the image quality of the conventional microscope superior, facilitating technical ease. The present study demonstrates the potential of 3D HD video systems to replace current binocular microscopes, offering qualitatively-equivalent microvascular anastomosis with improved comfort for experienced microsurgeons. However, image quality was rated inferior with the 3D HD system resulting in prolonged anastomosis times. Microsurgical skill acquisition in novice microsurgeons was not influenced by the viewing system used.